Monitoreofitosanitario de las plagas de banano en dosfincas convencionales y dosorgánicas en el cantón de Santa Rosa - Macas Ocampo, Héctor Heraldo (2013)
With the objective of carry out an essay on phytosanitary monitoring of plagues in banana cultivars, in conventional and organic banana plantations located in Santa Rosa canton, the following objectives were planned: 1.- To make a phytosanitary monitoring on banana cultivars in two conventional farms and in two organic farms in Santa Rosa canton; 2.- To study the population level for each plague found at the above mentioned farms. In order to accomplish the first objectives, two conventional banana farms were monitored: “El Porvenir”and “La Garcia”, and two farms with organic qualification: “El Santísimo” and “Bella Maria”. With this purpose, five referential points at random were located at the selected farm. Located a point at random, from the point L two transceptors were taken in the form of L, on which 10 plants ready and next to emerge were examined. The damage of defolier plagues at each of the ten selected plants was registered, and then identified to establish the percentage of damage caused by plagues on leaves and ryzhomes. The bunch was examined witch the help of a ladder. The total number of observed plants at the sampling site was 50. Each sampled plant came from a different site of research, and first was investigated the feeding behavior of different insects. After compiled the data, they were tabulated and made the statistics calculations in order to compare the percentage of damage caused in the banana cultivars at different sites of the research, giving the answer that we will find different plagues and insects in any place of the canton, but increased numbers in others, and that the natural enemies of insects are the key factor for the ecologic control of the different plagues in banana plantations organic or conventional.